Cartography of synthesis and the horizontal and vertical scales of the landscape: study on susceptibility to flooding and inundation in Lavras - MG - Santos, Thiago Gonçalves; Ventorini, Sílvia Elena; Zacharias, Andréa Aparecida (Revista do Departamento de Geografia, 2023)
Floods are the most recurrent disasters in Brazil in recent years; thus, knowledge of the natural dynamics of watercourses during the rainy season is extremely important, because it helps to reduce the damage caused by floods. The occupation of these areas corresponds to one of the main actions that will cause impacts during the rainy season, causing damage to the population through the occurrence of inundation that occupy the entire floodplain area. This article aims to present the synthesis cartography in detailing the susceptibility to inundation from cartographic and secondary data on a microscale, so that the results contribute to systematize methodological proposals in accordance with the Environmental Cartography assumptions. The studied area comprises a stretch of the Ribeirão Vermelho floodplain, located in Esplanada neighborhood, urban area of Lavras/MG, Brazil. The theoretical-methodological foundation was based on the General Theory of Systems applied in Physical Geography. The materials are made up of microscale cartographic and secondary data, which were organized and carried on ArcGis® 10.7. From the analytical mapping of topographic and anthropic conditions in the area, it was possible to carry out the analysis of the landscape vertical and horizontal structure. The results indicate the degree of susceptibility to floods and inundations from the organization of the classes from Very Low (1) to Very High (5), subdivided into sectors according to the relevance of systemic interactions.